PEMBERDAYAAN MASYARAKAT MELALUI PRODUK UMKM “BOCA NARI (BUBUK OLAHAN CABAI SINAR SARI)” SEBAGAI UPAYA PENINGKATAN PRODUK INOVATIF - Ermawansyah Ermawansyah; Alrahma Yunida; Dista Chaniara; Kasyiron Kasyiron; Mala Kustiasari; Maysy Fatimah; Nadila Nadila; Nora Cantika; Nur Afifah; Siski Marshanda; Sasih Karnita Arafatun (LPPM Universitas Bina Bangsa, 2023)
The Problem that occurs in chili- producing areas is that abudant yields can affect prices which at times experince unstable prices. When the proce of chili descreased, people were restless. University Of Muhammdiyah Bangk Belitung (UNMUH BABEL) students assitested in finding solutions to the problems of Sinar Sari villagers, especially KWT regarding the low sales of cayenne pepper and damaged chili quality. The method used is in the form of socialization and counseling in the proccesing of chili powder form is one of the bussines opportunities than can increase the selling value of chilies and have a long shelf life that is not easly damaged. Form chili powder products produce higher price than selling in the form of fresh chili. So that yoy get a bigger profit because chilies that are of poor qualty (broken and weak) can be produced into chili powder. To get a product that is that is worth selling, a marketing strategy is needed and the manufacture of a product label that is unique to Sinar Sari village. The brand we chose as the product name for chili powder is “BOCA NARI”. It is hoped that this name will be unique from the chili powder product of Sinar Sari village. Marketing is done thorught social media Facebook, Instagram, Shoope, and Whats App